Periodontal complications with obesity. Issue 1 (9th September 2018) - Suvan, Jean E.; Finer, Nicholas; D'Aiuto, Francesco
Abstract: The purpose of this paper was to identify and summarize current evidence describing periodontal complications associated with obesity. Electronic searches supplemented with manual searches were carried out to identify relevant systematic reviews. Identification, screening, eligibility, and inclusion of studies were performed independently by two reviewers. A MeaSurement Tool to Assess systematic Reviews (AMSTAR) was used to assess the quality and risk of bias of the included reviews. From 430 titles and abstracts screened, 14 systematic reviews were considered as eligible for inclusion in this meta‐review. Eight reviews reported on cross‐sectional studies investigating the association of obesity and periodontal diseases, 4 included longitudinal studies, 5 addressed response to periodontal therapy, 5 reported on studies investigating biomarkers, and only 2 were related to pediatric population samples. Systematic review summaries in the various study design domains (cross‐sectional, longitudinal and experimental) report that obese individuals are more likely to have periodontal diseases, with more severe periodontal conditions, than nonobese individuals, with cross‐sectional evidence congruent with longitudinal studies showing that obesity or weight gain increases the risk of periodontitis onset and progression. Published research on the effect of obesity on responses to periodontal therapy, or systemic or local biomarkers of inflammation, is variable and therefore inconclusive based on the evidence currently available, which suggests that overweight/obesity contributes to periodontal complications independently of other risk factors, such as age, gender, smoking, or ethnicity. This evidence supports the need for risk assessments for individual patients to facilitate personalized approaches in order to prevent and treat periodontal diseases.